The effect of nickel as a nickel chromium restoration corrosion product on gingival fibroblast through analysis of BCl-2 - FX Ady Soesetijo; Mandojo Rukmo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Restoration of NiCr may undergo corrosion process in artificial saliva. Corrosion product is soluble Ni substances in salivary electrolytes. Ni2+ may freely enter the cells through passive transport DMT-1. Ni2+ in the cell causes initiation of the ROS formation,which subsequently can conduct the redoxs reactions leading to DNA damage. The damage DNA affects the genetic expression, especially bcl-2, and even triggers apoptosis. Purpose: The aim of this study was to reveal the mechanism of Ni toxicity as a corrosion product of NiCr restoration on gingival fibroblasts through expression analysis of Bcl-2. Methods: Cells with a density of 105 planted on each coverslip in 72 wells to the treatment group and 24 wells to the control group (24 hours incubation). In the treatment groups, each well exposed with 20 μL artificial saliva containing Ni concentration results immerse each restoration, whereas the control group was exposed to 20 μL artificial saliva (incubation 1, 3, and 7 days). The data collected were subsequently analyzed using two-ways ANOVA, followed by one-way ANOVA. Comparing between experimental groups after one-way ANOVA was conducted using Fisher’s LSD. Whereas, the calculation and documentation of Bcl-2 expression was performed camera of Olympus Microscope BX-50 Japan. Results: Statistical analysis of two-ways ANOVA showed the presence of interaction between the increasing Ni concentration and exposure duration on the expression of Bcl-2 gingival fibroblasts (p=0.021<a=0.05). Conclusion: It can be concluded that the higher concentration of Ni exposed to gingival fibroblasts, and the longer incubation time will decreased Bcl-2 expression.Latar belakang: Restorasi NiCr dapat mengalami proses korosi di dalam saliva artificial. Produk korosi yang dihasilkan adalah substansi Ni yang terlarut di dalam elektrolit saliva. Ni2+ bebas dapat memasuki sel (fibroblas gingiva) melalui transport pasif DMT-1. Ni2+ di dalam sel menginisiasi pembentukan ROS, yang selanjutnya dapat menjalankan reaksi redoks dan dapat menimbulkan kerusakan DNA. DNA yang rusak mempengaruhi ekspresi genetik, terutama Bcl-2 dan bahkan dapat memicu apoptosis. Tujuan: Tujuan penelitian ini adalah untuk mengungkap mekanisme toksisitas Ni sebagai suatu produk korosi restorasi NiCr pada fibroblas gingiva melalui analisis ekspresi Bcl-2. Metode: Sel dengan kepadatan 105 ditanam pada tiap-tiap coverslip di dalam 72 well untuk kelompok perlakuan dan ditanam pada tiap-tiap coverslip di dalam 24 well untuk kelompok kontrol (inkubasi selama 24 jam). Pada kelompok perlakuan, masing-masing well dipapar dengan 20 μL saliva artificial yang mengandung konsentrasi Ni hasil perendaman tiap-tiap restorasi, sedangkan pada kelompok kontrol dipapar 20 μL saliva artificial (inkubasi 1,3 dan 7 hari). Data yang terkumpul selanjutnya dianalisis menggunakan ANOVA dua arah dan ANOVA satu arah. Perbandingan antar kelompok eksperimental setelah analisis ANOVA satu arah menggunakan uji Fisher’s LSD. Penghitungan jumlah sel yang mengekspresikan Bcl-2, kemudian dilanjutkan dengan dokumentasi dengan menggunakan kamera Olympus Microscope BX-50 Japan. Hasil: Analisis statistik ANOVA dua arah menunjukkan adanya interaksi antara peningkatan konsentrasi Ni dan lama paparan terhadap ekspresi Bcl-2 fibroblas gingiva > (p = 0,021 < á = 0,05). Kesimpulan: Dapat disimpulkan bahwa semakin tinggi konsentrasi paparan Ni pada fibroblas gingiva dan semakin lama masa inkubasi, maka akan menurunkan ekspresi Bcl-2.